The OPTICA study (Optimised Computed Tomography Pulmonary Angiography in Pregnancy Quality and Safety study): Rationale and design of a prospective trial assessing the quality and safety of an optimised CTPA protocol in pregnancy. Issue 177 (May 2019) - Gillespie, Ciara; Foley, Shane; Rowan, Michael; Ewins, Karl; NiAinle, Fionnuala; MacMahon, Peter
Abstract: Background: CTPA is the gold standard investigation for evaluating suspected pulmonary embolism (PE) in the general population however is sometimes considered second line in pregnant and post-partum patients with a normal CXR due to its higher breast dose and the increased radio-sensitivity of breast tissue during this period. Guidelines advocating for scintigraphy over CTPA, however, quote significantly higher breast doses than those achievable with optimised low dose strategies. Defining the radiation dose achievable with a specific low-dose CTPA protocol is therefore imperative. As decreasing dose is associated with increased image noise, demonstrating the image quality and validity of a negative low-dose CTPA in out-ruling PE in this population is necessary. Methods: The OPTICA study is a prospective multicentre observational study aiming to validate the clinical utility and safety of an optimised low-dose CTPA protocol in pregnancy. An optimised low-dose CTPA protocol has been agreed across all study sites with equivalent CT capabilities. Pregnant women undergoing CTPA for suspected PE will be included. Independent review of CTPAs by two radiology consultants, image data analysis and 3-month patient follow up will be performed. The primary outcome is the 3-month incidence of VTE in pregnant patients in whom PE was excluded at baseline CTPA. Secondary outcomes will confirm the associated radiation dose and image quality of this protocol. The radiation dose will be calculated using the Monte Carlo method and will include maternal effective, breast and foetal doses. Image quality will be assessed objectively by measuring opacification of the main pulmonary trunk, signal-to-noise and contrast-to-noise ratios and subjectively using a grading scale and inter-reader variability of CTPA results. Conclusion: The OPTICA study is the first prospective trial of a low-dose CTPA protocol in the pregnant population. It will provide high-quality evidence defining the achievable dose, image quality and safety of an optimised CTPA for this population. It will assist other institutes with similar CT capabilities in achieving comparable low doses for its patients and provide an evidence base upon which modern CTPA protocols can be appropriately compared to scintigraphy in the pregnant population. Highlights: NPV and inconclusive rates are similar for CTPA and scintigraphy in pregnancy. A lower breast radiation dose is the main advantage of scintigraphy over CTPA. CTPA offers alternative diagnoses, lower foetal dose, speed and ease of access. Modern CT protocols permit lower doses than are quoted in the literature for this population. Low-dose CTPA protocols have not been studied in this population. This trial prospectively evaluates the safety of a low-dose CTPA protocol in pregnancy.